Pengembangan Pembelajaran PPBA Berbasis Problem Based Learning Dalam Meningkatkan Hasil Belajar Santri di Pondok Pesantren Ngalah - Rofiqotul Kamilia; M. Anang Sholikhudin; Muhammad Nur Hadi; Askhabul Kirom (4, 2025)
This study aims to develop a Problem Based Learning (PBL) learning model in Dormitory I of Ngalah Islamic Boarding School, while identifying supporting and inhibiting factors in the development process, and evaluating its impact on student learning outcomes. The study used a qualitative approach with Research and Development (R&D) type, which was implemented through the stages of needs analysis, design, trial, and evaluation. Data were collected using observation, interview, and documentation techniques, so as to obtain a comprehensive picture of the implementation of the PBL model in the dormitory environment. The results showed that the implementation of the PBL learning model was significantly able to increase the active involvement of students in the learning process. PBL encourages students to think critically, work together, and find solutions to contextual problems. The implementation of this model has proven effective in improving learning outcomes, where the level of student learning completion increased from 36.36% to 72.73%. This success was supported by the active role of the guardian, the availability of learning resources, and a conducive learning atmosphere in the dormitory. However, several obstacles were also identified, such as limited study time outside of routine Islamic boarding school activities, differences in students' initial abilities, and the lack of utilization of modern learning media. To achieve more optimal results, efforts need to be made to minimize these obstacles by adjusting schedules, improving facilitator skills, and providing a more varied learning media. Overall, these findings provide important implications for the development of learning models in Islamic boarding schools, particularly in adopting PBL as an effective strategy to improve the quality and completeness of student learning outcomes.. Abstrak Penelitian ini bertujuan untuk mengembangkan model pembelajaran berbasis Problem Based Learning (PBL) di Asrama I Pondok Pesantren Ngalah, sekaligus mengidentifikasi faktor-faktor pendukung dan penghambat dalam proses pengembangannya, serta mengevaluasi dampaknya terhadap hasil belajar santri. Penelitian menggunakan pendekatan kualitatif dengan jenis Research and Development (R&D), yang dilaksanakan melalui tahapan analisis kebutuhan, perancangan, uji coba, dan evaluasi. Data dikumpulkan menggunakan teknik observasi, wawancara, dan dokumentasi, sehingga diperoleh gambaran yang komprehensif mengenai penerapan model PBL di lingkungan asrama. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran PBL secara signifikan mampu meningkatkan keterlibatan aktif santri dalam proses belajar. PBL mendorong santri untuk berpikir kritis, bekerja sama, dan mencari solusi atas permasalahan yang bersifat kontekstual. Implementasi model ini terbukti efektif dalam meningkatkan hasil belajar, di mana tingkat ketuntasan belajar santri meningkat dari 36,36% menjadi 72,73%. Keberhasilan ini didukung oleh peran aktif pengasuh, ketersediaan sumber belajar, serta suasana belajar yang kondusif di asrama. Namun demikian, ditemukan pula beberapa hambatan, seperti keterbatasan waktu belajar di luar kegiatan rutin pesantren, perbedaan kemampuan awal santri, dan kurangnya pemanfaatan media pembelajaran modern. Untuk mencapai hasil yang lebih optimal, perlu dilakukan upaya meminimalisir hambatan tersebut melalui penyesuaian jadwal, peningkatan keterampilan fasilitator, dan pengadaan media pembelajaran yang lebih variatif. Secara keseluruhan, temuan ini memberikan implikasi penting bagi pengembangan model pembelajaran di pondok pesantren, khususnya dalam mengadopsi PBL sebagai strategi efektif untuk meningkatkan kualitas dan ketuntasan hasil belajar santri.